„Taka jak na obrazie”. O Sydonii von Borck w powieściach Elżbiety Cherezińskiej i Teresy Bojarskiej - Dynkowska, Julia (Zagadnienia Rodzajów Literackich, 2025)
This paper focuses on Sidonia von Borck, a Pomeranian noblewoman accused of witchcraft and executed in 1620. Sidonia’s literary history has been inextricably intertwined with (primarily) visual arts from its very beginnings. This is evident not only in the Pre-Raphaelite fascination with her character (stemming from their admiration for Wilhelm Meinhold’s Sidonia the Sorceress) but also in the novels of contemporary authors. The following novels serve as research material: Sydonia. Słowo się rzekło by Elżbieta Cherezińska (2023), Na jednym płótnie by Teresa Bojarska (1974), I also refer briefly to Wieloryb. Wypisy źródłowe by Jerzy Limon (1998). The inspiration for the apocryphal additions in the mentioned novels are, among others, paintings such as: Double portrait of Sidonia von Borck as a young and old woman, attributed to the Cranachs’ workshop, The Croy Tapestry by Peter Heymans, The Family tree of the Griffin family painted by Cornelius Krommeny, or The Portrait of the Duke of Pomerania Philip I painted by Lucas Cranach the Younger. The first part of the article is also devoted to explaining the aforementioned fascination of the Pre-Raphaelites with Sidonia von Borcke, which resulted in the creation of the painting considered to be her most famous portrait, i.e. Sidonia von Borck, 1560 by Sir Edward Burne-Jones.